Hepatocellular carcinoma in older adults: A comprehensive review by Young International Society of Geriatric Oncology. Issue 4 (May 2020) - Arora, Sukeshi Patel; Liposits, Gabor; Caird, Susan; Dunne, Richard F.; Moffat, Gordon Taylor; Okonji, David; Rodriquenz, Maria Grazia; Dua, Divyanshu; Dotan, Efrat
Abstract: Given the prevalence and the rising incidence of hepatocellular carcinoma (HCC) in older adults worldwide, there is an urgent need to improve our understanding of the implications of treatment modalities in this population. The care of older patients with HCC is challenging due to the lack of evidence-based recommendations in this population. The current treatment approach for older patients relies on extrapolation of data from clinical trials conducted mostly in younger patients or fit older adults. Further, in the last few years, the arsenal of systemic treatments has increased with currently seven FDA-approved therapies available for patients with advanced HCC. Therefore, understanding how to apply current data to this unique and diverse patient population is necessary. This review will aim to shed light on the approach to older adults with HCC through an assessment of available data in the literature.